2008
DOI: 10.1111/j.1467-6486.2008.00771.x
|View full text |Cite
|
Sign up to set email alerts
|

Inter‐ and Intra‐Organizational Knowledge Transfer: A Meta‐Analytic Review and Assessment of its Antecedents and Consequences

Abstract: Research on organizational knowledge transfer is burgeoning, and yet our understanding of its antecedents and consequences remains rather unclear. Although conceptual and qualitative reviews of the organizational knowledge transfer literature have emerged, no study has attempted to summarize previous quantitative empirical findings. As a first step towards that goal, we use meta-analytic techniques to examine how knowledge, organization and network level antecedents differentially impact organizational knowled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
813
2
35

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 990 publications
(874 citation statements)
references
References 138 publications
(169 reference statements)
24
813
2
35
Order By: Relevance
“…Also, a consistent positive relationship between a relevant structural characteristic: tie strength, and knowledge transfer has been found in prior research (Rowley, Behrens, & Krackhardt 2000;Reagans & McEvily 2003;van Wijk, Jansen, & Lyles 2008). Tie strength refers to 'the closeness and interaction frequency of a relationship between two parties' (Levin & Cross 2004, p. 1478Hansen 1999).…”
Section: Client Trust and Relationship Length With The Financial Advimentioning
confidence: 84%
“…Also, a consistent positive relationship between a relevant structural characteristic: tie strength, and knowledge transfer has been found in prior research (Rowley, Behrens, & Krackhardt 2000;Reagans & McEvily 2003;van Wijk, Jansen, & Lyles 2008). Tie strength refers to 'the closeness and interaction frequency of a relationship between two parties' (Levin & Cross 2004, p. 1478Hansen 1999).…”
Section: Client Trust and Relationship Length With The Financial Advimentioning
confidence: 84%
“…This introduced theoretical variation into our investigation of subsidiary managers" practices in mobilizing knowledge. The focal subsidiaries were of different sizes, indicating different levels of knowledge stocks (Gupta & Govindarajan, 2000;van Wijk, Jansen, & Lyles, 2008), and had different numbers and types of mandates, a sign of the concentration and scope of their knowledge (Gupta & Govindarajan, 2000;Hansen & Løvås, 2004;van Wijk et al, 2008). In addition, the structure of the MNCs" international operations varied sufficiently to incorporate local, regional and global subsidiary responsibilities.…”
Section: Research Design and Settingmentioning
confidence: 99%
“…Moreover, the evidence of size on incremental and radical innovation performance reports contradictory results; although knowledge accumulation is one of the antecedents of innovation performance that, along with size, has been most widely studied, relatively little empirical research has been reported on the effect of size on internal knowledge creation capability and absorptive capability. The studies that assess the effect of size on knowledge management capabilities focus on knowledge transfer, also reporting inconclusive results (van Wijk et al, 2008). For this reason the present study aims to unravel the impact of organizational size on both radical and incremental innovation performance, and on the main knowledge accumulation capabilities that determine them, which will reveal in greater detail the complex antecedents and their interactions that intervene in the development of the innovation process.…”
Section: Introductionmentioning
confidence: 99%
“…However, the literature identifying the key aspects to develop innovation performance based on knowledge accumulation capabilities (Jiménez-Jiménez and Sanz-Valle, 2011) requires additional conceptual and empirical research (Kim et al, 2012;van Wijk et al, 2008). Firms can accumulate new knowledge by generating it internally, through a process of internal knowledge creation grounded on the skills, knowledge and experiences of their employees (Smith et al, 2005), by acquiring it from external sources through the development of their absorptive capability (Cohen and Levinthal, 1990), or by implementing a strategy to accumulate new knowledge that combines both these options.…”
Section: Introductionmentioning
confidence: 99%